Outer Solar System Prospective Energy and Material Resources (Springer International Publishing, 2018)
The Earth has limited resources while the resources in space are virtually unlimited. Further development of humanity will require going beyond our planet and exploring of extraterrestrial bodies and their resources. This book investigates Outer Solar Systems and their prospective energy and material resources. It presents past missions and future technologies and solutions to old problems that could become reality in our life time. The book therefore is a great resource of condensed information for specialists interested in current and impending Outer Solar Systems related activities and a good starting point for space researchers, inventors, technologists and potential investors.